Design and Fabrication of Digital Microfluidics device for Lab-on-a-Chip Applications - Hammas Ullah; Faraz Shoaib; Syed Danyal Zahid; Mohammad Iymaan Mahmood; Mubashar Ali; Moazzam Ali; Hamza Abbas; Ali Turab Jafry (Engineering Proceedings, 2023)
In digital microfluidics, discrete liquid droplets move on a dielectric surface with the help of AC or DC voltage. Digital microfluidics system has extended the scope of microfluidics by providing automated, precise flow control for point-of-care devices capable of medical diagnostics, environmental, and chemical sensing platforms. In this paper, we introduce a digital microfluidics platform based on electrowetting on a dielectric using PCB substrate designed on Easy EDA software. The platform’s performance was analyzed at various DC voltages between 200 V and 400 V for droplet actuation. PCB fabrication, the utilization of easily accessible and cheap materials such as cooking oil and grafting tape as a dielectric layer, allowed the fabrication to be affordable and simple. The results indicate that droplet actuation takes place at 220 V. The droplet velocity obtained was 2.6 mm/s and 1.51 mm/s using silicon oil and cooking oil, respectively, at 400 V. Our proposed digital microfluidics platform will play a vital role in droplet actuation and can be used for diagnostic applications such as DNA analysis and cell culture due to its simple fabrication and cost-effective technique.